Unraveling the Mechanisms of Cutaneous Graft-Versus-Host Disease - Santos e Sousa, Pedro; Bennett, Clare L.; Chakraverty, Ronjon (Frontiers in Immunology, 2018)
The skin is the most common target organ affected by graft-versus-host disease (GVHD), with severity and response to therapy representing important predictors of patient survival. Although many of the initiating events in GVHD pathogenesis have been defined, less is known about why treatment resistance occurs or why there is often a permanent failure to restore tissue homeostasis. Emerging data suggest that the unique immune microenvironment in the skin is responsible for defining location- and context-specific mechanisms of injury that are distinct from those involved in other target organs. In this review, we address recent advances in our understanding of GVHD biology in the skin and outline the new research themes that will ultimately enable design of precision therapies.